1995
DOI: 10.1086/176139
|View full text |Cite
|
Sign up to set email alerts
|

Exact Solutions for Steady State Incompressible Magnetic Reconnection

Abstract: The problem of steady state magnetic reconnection in incompressible, resistive plasmas is addressed. It is shown that families of exact analytic solutions can be derived by exploiting the formal symmetry between the magnetic field lines and the streamlines of the flow. These solutions, while incorporating previous models for antiparallel magnetic merging, assume no inherent topological symmetry for the reconnective geometry. It is demonstrated that fast reconnection occurs within a narrow X-type configuration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
78
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 15 publications
10
78
0
Order By: Relevance
“…As in Craig & Henton (1995), we observe that ''fast'' reconnection solutions, for which the electric field E at the X-point scales independently of the resistivity, can in principle always be constructed by a suitable choice of external boundary conditions. However, severe pressure constraints on the solution effectively limit the range of parameter space for which such fast solutions are valid (see Craig & Henton 1995;Craig & Watson 2000).…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…As in Craig & Henton (1995), we observe that ''fast'' reconnection solutions, for which the electric field E at the X-point scales independently of the resistivity, can in principle always be constructed by a suitable choice of external boundary conditions. However, severe pressure constraints on the solution effectively limit the range of parameter space for which such fast solutions are valid (see Craig & Henton 1995;Craig & Watson 2000).…”
Section: Introductionmentioning
confidence: 66%
“…One interesting advance in recent years was the discovery by Craig & Henton (1995) of an exact reconnection solution for resistive single-fluid plasmas. This simple two-dimensional solution has since been modified to include the effects of threedimensionality, time dependence, and different spatial geometries (Craig & Fabling 1996, 1998Watson & Craig 2002).…”
Section: Introductionmentioning
confidence: 99%
“…8 We have found that for modest levels of turbulence, the underlying large-scale features of the laminar solution are robust and even the intrinsic scalings of the problem with plasma resistivity are retained. Some modest enhancement of the energy dissipation is observed, but this is mainly due to the additional small-scale structures inherent in the turbulent initial conditions.…”
Section: Discussionmentioning
confidence: 83%
“…III we summarize the analytic solution of Ref. 8, and in Sec. IV we develop a simple analytic timedependent solution that indicates the behavior of the individual Fourier modes in a full 2D simulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation